Legal Protection (Rechtsbecherming) Against The Entry Of A Third Party In The Administrative High Court - David Pasaribu (PT Justitia Legal Research, 2025)
The acceptance of third parties at the appellate level is a discourse that requires in-depth theoretical studies. Law Number 5 of 1986 about Administrative Courts and its amendments do not clearly regulate third parties at the appellate level. This condition has led to the emergence of propaganda from a progressive legal perspective to accommodate third parties at the appellate level for supporting the existentiality of legal protection for justice seekers. This research aims to analyze the acceptance of third parties at the appellate level from the perspective of legal protection, the technical concept of administration, and the trial of the acceptance of third parties at PTTUN. The research method is normative juridical with conceptual and statutory approaches. The results show that third parties are allowed to enter the examination at the appellate level in the context of legal protection, correction of legal error, exploring material truth, and upholding substantive justice. The author offers a technical concept of administration and trial of third-party entry at the PTTUN by submitting an application and its additional documents to the PTSP of PTUN. Furthermore, Judges of PTTUN responds to the third-party application through the interim decision. Furthermore, PTTUN or PTUN does the additional examination.